2009
DOI: 10.1002/macp.200990002
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Chem. Phys. 3–4/2009

Abstract: Cover: Highly ordered and robust monolayers of colloidal particles can be prepared by a simple and versatile floating method at the air-water interface. The floating monolayer can be efficiently transferred to corrugated and curved surfaces, allowing the stacking of complex layer architectures. Further details can be found in the article by M. Retsch, Z. Zhou, S. Rivera, M. Kappl, X. S. Zhao, U. Jonas, Q. Li on page 230.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 0 publications
0
77
0
Order By: Relevance
“…[55] It has been shown that monolayers, which were floated in the presence of surfactants, exhibited a higher mechanical stability and fractured less easily at the edges. [55] This higher stability facilitates the transfer to solid substrates as well. Additionally, free surfactant molecules can adsorb to the particle surfaces and introduce further negative charges.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[55] It has been shown that monolayers, which were floated in the presence of surfactants, exhibited a higher mechanical stability and fractured less easily at the edges. [55] This higher stability facilitates the transfer to solid substrates as well. Additionally, free surfactant molecules can adsorb to the particle surfaces and introduce further negative charges.…”
Section: Resultsmentioning
confidence: 99%
“…[55,93] Vortical deposition high/medium easy, fast arbitrary substrates [89] Direct assembly high/high easy, fast arbitrary substrates [94] , in this thesis 32 Theory…”
Section: Summary Of the Crystallization Methodsmentioning
confidence: 99%
See 3 more Smart Citations